Third World Women and Patriarchal Society in The Story of Zahra - Jihan Abdul Rahman Oshiesh (The Creative Launcher, 2020)
This article focuses on the relationship of Zahra; the heroine of the novel, The story of Zahra by Hanan al-Shaykh with "male" community. Zahra is not only the victim of her family but of an entire society also. Her father who is always cynical of her face which is full of pimples and expected spinsterhood, to her mother and her betrayal of her husband with her lover, to her spoiled and failed brother, her family friend who raped her and forced her to abort twice. Her failed marriage to a friend of her uncle and her return to her homeland, which seemed to be suffering from the scourge of war, and her belief in her ability to distract the mind of the sniper by establishing a relationship with him. Zahra couldn’t be an independent individual in her society, but a tool that everyone can see from his perspective. Zahra suffered from the oppression of the patriarchal society, which gave the man the oppression and abuse of women without any deterrent or a pretext for their oppression. Hanan al-Shaykh The Story of Zahra is a real example of what most women in the Third World suffer from the dominance of male society and their control over women, spiritually and physically.